TELEMEDICINE ACCEPTANCE AND USAGE IN JAKARTA METROPOLITAN AREA - Khrisna PT Malau; Bryany T Santi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Implementing infection prevention protocols during the COVID-19 pandemic in Indonesia hinders the public from accessing health care services. This condition causes virtual health services to become more accessible than conventional health services, thus encouraging healthcare providers to adopt telemedicine as a method of service delivery. However, as a relatively new technology in Indonesia, public acceptance is crucial to predict the level of public willingness to adopt telemedicine. Yet, a little study in Indonesia has tried to assess it. Purposes: The purpose of this research is to measure the acceptability of telemedicine services in Jakarta metropolitan area, the factors that determine it, and whether the level of acceptance correlates with the usage frequency of telemedicine. Methods: Data used in this study is acquired with an online survey from February to March 2022, targeting residents of the Greater Jakarta area. Instruments used in this survey are demographic data form and SUTAQ questionnaire translated into Indonesian. Of the total 454 respondents, 200 have used telemedicine in the last six months. Respondents were then divided into several groups based on age, gender, monthly income, education level, chronic conditions, health insurance membership, and frequency of telemedicine use. Bivariate analysis was conducted using chi-square test for categorical data and t-test for numerical data. Results: The assessment of the SUTAQ scores indicates good acceptance of telemedicine in all demographic groups. Increased accessibility to health services and satisfactory user experience have contributed to its good acceptance. However, we also found that the frequency of use was not correlated with the level of acceptance, but positively correlated with the presence of chronic conditions. Conclusions: Telemedicine is well received by users who live in the Greater Jakarta area. Users find it easier to access health services and are satisfied with the health services provided through telemedicine.